Perancangan Sistem Informasi Fasilitas Fitness Gym Berbasis Website Menggunakan Codeigniter - Muhammad Ridwan; Zuhri Halim (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
In the era of advancing information technology, effective data and information processing is crucial. Especially in the fitness field, tools such as computers and web-based applications have become integral. This research aims to improve the methods used by Gym Predator. Using a waterfall technique approach consisting of five stages: requirements, design, implementation, testing, and maintenance, this research developed a web-based application using the CodeIgniter framework. This application is customized to the specific needs of Gym Predator. The findings are presented in the form of a website that not only meets the demands of the gym, but also enhances the user experience in finding information and using the gym's services. Continuous evaluation and enhancement of the website will increase user interactivity, provide clearer information, and improve navigation. The findings of this study not only contribute to designing and developing better gym websites, but also underscore the importance of positive user experience in the fitness industry.